Rethinking the geography of gentrification: From a scale perspective. Issue 118 (January 2021) - Liu, Cheng; Deng, Yu; Song, Weixuan; Gong, Jian; Zeng, Jie
Highlights: Re-scaling has superior explanatory power for geography of gentrification. Flow is a point of departure and reference for theoretical and comparative study. Re-scaling informs resistance ontologically and epistemologically. Abstract: This article proposes that the lens of scale may potentially yield fresh insights into the comparative research on gentrification. First, the flows of capital, people, and knowledge in re-scaling furnish a point of departure for a holistic theory of planetary gentrification and a vital reference point for comparison. Second, to harness upscaling and downscaling in tandem, comparative studies should adequately connect gentrification with similar regional/local ontologies to obtain greater ontological power. The disadvantaged should take advantage of a loose and shifting alliance among the pro-gentrification forces to find a "real choice" (instead of a "perfect choice") for those affected. Moreover, a pragmatic solution is opprobrium against predatory flows, particularly the flows of capital, whose nature is defined by local peculiarities.